PENGARUH PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN TIKET BIOSKOP PADA SITUS TIX.ID (STUDI PADA PENGGUNA APLIKASI TIX.ID DI KOTA SAMARINDA) - Anggraeni, Alvin Nurul (EKONOMIA, 2019)
Alvin Nurul Anggraeni: Effects of Consumer Behavior on Cinema Ticket Purchase Decisions on Tix.id Site (Study of Tix.id Application Users in Samarinda City). Under the guidance of Ms. Mardiana as the first lecturer and Ms. Nurfitriani as the second lecturer.          The purpose of this study was to determine cultural factors, social factors, personal factors and psychological factors on the decision to buy cinema tickets on the Tix.id site. The theory used in this study is consumer behavior, cultural factors, social factors, personal factors, psychological factors and purchasing decisions. This research was conducted on Tix application users, id in Samarinda City, with a sample of 100 respondents using purposive sampling method. Data collection by distributing questionnaires online using the Likert scale to measure each indicator. The analysis technique used is multiple linear regression analysis.         The results of this study indicate that cultural factors have a positive and significant effect on the decision to purchase cinema tickets on the Tix.id site. Social factors have an effect not positive and not significant on the decision to buy cinema tickets on the Tix.id site. Personal factors have an effect not positive and not significant on the decision to buy cinema tickets on the Tix.id site. Psychological factors have a positive and significant effect on the decision to purchase cinema tickets on the Tix.id site. Cultural factors, social factors, personal factors and psychological factors together have a positive and significant effect on the decision to purchase cinema tickets on the Tix.id site.